Nonlinear Formulation of Multicomponent Reactive Transport With Species‐Specific Dispersion Properties - Rodrigo Pérez‐Illanes; Maarten W. Saaltink; Daniel Fernàndez‐Garcia (Water Resources Research)
Abstract The modeling of reactive transport through porous media is a challenging numerical problem. Methods of solution have leveraged the stoichiometry of chemical reactions to address the transport of multiple aqueous species by expressing them in terms of an equivalent, linearly independent variable (component). This approach effectively decouples advection‐dispersion transport from the source terms associated with equilibrium reactions. A common assumption found in the literature is that all species disperse with the same transport coefficients. Recent experimental studies have discussed that this is not necessarily the case, particularly for transverse mixing, which is limited by the species‐specific molecular diffusion. This article presents a formulation of multicomponent reactive transport that takes into account the differences in dispersion coefficients. These differences lead to a nonlinear transport equation for the components, from where an expression for evaluating reaction rates is derived. It is demonstrated that this expression simplifies to the well‐known equations assuming the same dispersion for all species. Numerical simulations of a binary chemical system under diffusion‐ and advection‐dominated transport conditions are used to evaluate the influence that differential transport coefficients have upon the output of chemical reactions. Results indicate that differences in transport coefficients are particularly relevant when the chemical signature of the input solutions is not strongly dominated by one of the species in the component. Unexpectedly, this opens the possibility to mineral dissolution coexisting with precipitation during the mixing of two waters in equilibrium. This phenomenon can be explained by nonlinear mixing processes proportional to the differences in transport coefficients.